The Stony Brook awake craniotomy protocol: A technical note. (September 2019) - Shen, Erica; Calandra, Colleen; Geralemou, Sofia; Page, Christopher; Davis, Raphael; Andraous, Wesam; Mikell, Charles
Highlights: Avoidance of rigid head fixation and use of intubation for the opening and closure. Allows for a "game-time" decision about whether to wake the patient up for mapping. Helps to maximize patient and physician comfort while allowing for successful tumor resection. Abstract: Most current awake craniotomy techniques utilize unnecessarily complicated airway management, and cause discomfort to the patients during the awake phase of the surgery. Our manuscript is written to discuss the neurosurgical and anesthetic techniques that we have developed to optimize awake craniotomy techniques at Stony Brook University Medical Center. We used the frameless Brainlab™ skull-mounted array for stereotactic navigation. Rigid fixation of the skull was avoided. General anesthesia with established airway was used during the "asleep" phase of the surgery. Following the removal of the bone flap and the opening of the dura, the patients were woken up, and the established airway was removed. Cortical mapping was performed to establish a safe entry zone for tumor removal. While the tumors were being removed, we continued motor examination and casual conversation with the patients to ensure safety. Patients were sedated during the remaining phase of the surgery until skin closure. No patient exhibited any neurological deficits or adverse anesthesia outcomes during the postoperative period. The protocol we developed avoids rigid skull fixation and emphasizes flexible intraoperative planning, thereby maximizing patient and physician comfort while allowing for successful tumor resection.